2018
DOI: 10.1186/s12894-018-0400-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of endoscopic enucleation of the prostate with thulium fiber laser on the erectile function

Abstract: BackgroundThe impact of number of endoscopic enucleation of the prostate techniques (holmium laser enucleation - HoLEP for example) on erectile function have already been investigated. However, the thulium-fiber laser, in this setting remains unstudied. In this study, we compared sexual function outcomes in patients with benign prostatic hyperplasia (BPH) treated with transurethral resection of the prostate (TURP) or thulium-fiber laser enucleation (ThuFLEP).MethodsWe performed a retrospective analysis of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 24 publications
1
28
0
5
Order By: Relevance
“…The present results confirmed the high efficacy of both Tm‐fiber enucleation and TURP in the management of LUTS and benign prostatic obstruction. Both techniques had favorable functional outcomes that had previously been proven in a number of trials . No difference between resection and enucleation was found.…”
Section: Discussionmentioning
confidence: 63%
“…The present results confirmed the high efficacy of both Tm‐fiber enucleation and TURP in the management of LUTS and benign prostatic obstruction. Both techniques had favorable functional outcomes that had previously been proven in a number of trials . No difference between resection and enucleation was found.…”
Section: Discussionmentioning
confidence: 63%
“…A further study compared ThuFLEP with Transurethral Resection of Prostate (TURP) for BPH, with both modalities being equally effective at resolving LUTS at 6 months postoperatively. 23 Interestingly, patients receiving ThuFLEP had a significant improvement in erectile function on average postoperatively. The authors suggest that this is due to TFL's shallower penetration depth, allowing safer incisions with a lower risk of surgical capsule penetration and therefore less damaging on neurovascular bundles at the posterolateral surface of the prostate.…”
Section: Prostate Laser Enucleationmentioning
confidence: 95%
“…22 In a retrospective study, Enikeev et al found ThuFLEP to significantly improve erectile function. 23…”
Section: Prostate Laser Enucleationmentioning
confidence: 99%
“…Erectile function after ThuLEP had no significant change in two prospective and two retrospective studies with sexual function defined as primary outcomes (Carmignani et al., 2015; Enikeev et al., 2018; Saredi et al., 2016; Wang, Shao, Lu, Lu, & Li, 2014). These might be explained by a consolidated enucleation technique with minimal capsular perforation and minimised energy conduction beyond capsule, reducing post‐operative neurapraxia (Saredi et al., 2016).…”
Section: Erectile Functionmentioning
confidence: 99%